(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
In this article, the category of case found in linguistics is often referred to as the category of case in nouns, the general meanings that indicate that the concept of object or subject belongs to one of the three persons, sometimes the subject, and the system of forms expressing these meanings. The article illustrates the similarity of the distribution of ownership units in English and Uzbek. For example, in English, the unit denoting possessive comes in the accusative case, while in Uzbek the component is given in the accusative case, the second component is expressed by the suffix person.